THE INTERNATIONALIZATION OF THE INTERNATIONAL CONTRACT ACCORDING TO INTERNATIONAL THEORIES AND CONVENTIONS - Al-Amaren, Emad Mohammed (Yustisia, 2018)
The contract generally means the consent of two wills to make a particular legal effect of giving or doing work or abstaining from work in return for material or in-kind compensation. As for the commercial nature of the contract, in the Jordanian civil law, the contract is considered commercial if it is included in the business stipulated in Article 6 of the Jordanian Trade Law. A contract is commercial if its subject matter is one of the acts provided for in article 6 of the Trade Law, as is the case with the purchase of movables for the purpose of selling them, and the agency commission and brokerage. On the international level, the commercial character of the contract comes closest to the extent to which the contract relates to international trade as the export or import of goods that regulate the movement of goods across the borders of one State. After the good study of the subject, we find that there are a number of questions or problems that accompany the determination of the internationality of the contract, including the extant of adequacy of the personal internationality, in addition to, whether the introduction of the purely national relationship to the jurisdiction of the foreign country lead to the internationalization of the relationship. The study will deal with international standards of the contract in different international theories and conventions. I will discuss the legal and economic standard in section I, the mixed standard in section II and the standards of the internationality of the contract in accordance to international conventions, especially the Vienna Conventions, The Hague Convention, the Rome Convention and the International Convention on International Arbitration in Section III.